KESIAPAN LEMBAGA SEKOLAH DALAM PELAKSANAAN PENDIDIKAN KARAKTER SISWA DI SMA NEGERI 1 BATANG - Hadiarti, Safitri (Solidarity: Journal of Education, Society and Culture, 2013)
National education aims to score a winning nation generation, both in science and technology capability and superior in terms of his noble character. Character-based education should be developed in the world of education in Indonesia in an effort to achieve national education goals. Implemented character education is very important to build quality human resources. The study uses descriptive qualitative research methods. Research sites in SMA Negeri 1 Batang. Subjects in this study were principals, deputy principals and the public relations field facilities, three teachers, the head of the TU. Data collection techniques used were observation, interview and documentation. The validity of the data used is the technique of data triangulation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions or verification. The results show that character education in SMA 1 Batang emphasizes the value of religious, honest, caring environment, nationalism, orderly, disciplined, but the main value of instilling order and discipline. Character education is not a separate subject but put all these subjects, forms of integration of character education can be seen from the syllabus and lesson plans developed by teachers in SMA 1 Batang. Obstacles in the implementation of character education is a different thinking, a wrong assumption on the advice of teachers, the difficulties in the preparation of syllabi and lesson plans, lack of student discipline.